x-(2+i)(2-i)(x+3)=

Simple and best practice solution for x-(2+i)(2-i)(x+3)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x-(2+i)(2-i)(x+3)= equation:


Simplifying
x + -1(2 + i)(2 + -1i)(x + 3) = 0

Reorder the terms:
x + -1(2 + i)(2 + -1i)(3 + x) = 0

Multiply (2 + i) * (2 + -1i)
x + -1(2(2 + -1i) + i(2 + -1i))(3 + x) = 0
x + -1((2 * 2 + -1i * 2) + i(2 + -1i))(3 + x) = 0
x + -1((4 + -2i) + i(2 + -1i))(3 + x) = 0
x + -1(4 + -2i + (2 * i + -1i * i))(3 + x) = 0
x + -1(4 + -2i + (2i + -1i2))(3 + x) = 0

Combine like terms: -2i + 2i = 0
x + -1(4 + 0 + -1i2)(3 + x) = 0
x + -1(4 + -1i2)(3 + x) = 0

Multiply (4 + -1i2) * (3 + x)
x + -1(4(3 + x) + -1i2 * (3 + x)) = 0
x + -1((3 * 4 + x * 4) + -1i2 * (3 + x)) = 0
x + -1((12 + 4x) + -1i2 * (3 + x)) = 0
x + -1(12 + 4x + (3 * -1i2 + x * -1i2)) = 0
x + -1(12 + 4x + (-3i2 + -1i2x)) = 0

Reorder the terms:
x + -1(12 + -3i2 + -1i2x + 4x) = 0
x + -1(12 + -3i2 + -1i2x + 4x) = 0
x + (12 * -1 + -3i2 * -1 + -1i2x * -1 + 4x * -1) = 0
x + (-12 + 3i2 + 1i2x + -4x) = 0

Reorder the terms:
-12 + 3i2 + 1i2x + x + -4x = 0

Combine like terms: x + -4x = -3x
-12 + 3i2 + 1i2x + -3x = 0

Solving
-12 + 3i2 + 1i2x + -3x = 0

Solving for variable 'i'.

Move all terms containing i to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 3i2 + 1i2x + 12 + -3x = 0 + 12

Reorder the terms:
-12 + 12 + 3i2 + 1i2x + -3x = 0 + 12

Combine like terms: -12 + 12 = 0
0 + 3i2 + 1i2x + -3x = 0 + 12
3i2 + 1i2x + -3x = 0 + 12

Combine like terms: 0 + 12 = 12
3i2 + 1i2x + -3x = 12

Add '3x' to each side of the equation.
3i2 + 1i2x + -3x + 3x = 12 + 3x

Combine like terms: -3x + 3x = 0
3i2 + 1i2x + 0 = 12 + 3x
3i2 + 1i2x = 12 + 3x

Reorder the terms:
-12 + 3i2 + 1i2x + -3x = 12 + 3x + -12 + -3x

Reorder the terms:
-12 + 3i2 + 1i2x + -3x = 12 + -12 + 3x + -3x

Combine like terms: 12 + -12 = 0
-12 + 3i2 + 1i2x + -3x = 0 + 3x + -3x
-12 + 3i2 + 1i2x + -3x = 3x + -3x

Combine like terms: 3x + -3x = 0
-12 + 3i2 + 1i2x + -3x = 0

The solution to this equation could not be determined.

See similar equations:

| 8b-7b-b+2b+1=19 | | 15y-y+4y-9y-3=6 | | x-128/26 | | 2g-g+g+1=15 | | 2q-q-1=13 | | 3y-5(2y+4)=8 | | 20v-20v+4v+3=11 | | 1x=1.8x+32 | | cosx=-.53 | | 1x=1.8+32x | | -9=8+2x | | 3x-1/5-7-x/3 | | 0.99x+36=1.39x | | 2timesx= | | 4(-5-3x)=76 | | 7w-3w+3=19 | | 20x=-10 | | 40x=1.6 | | 4sin^2x+4-5=0 | | 40/x=8/5 | | 10x-6+10x=180 | | -4(-1x-5)=40 | | 3(6x+4)+5=-109 | | -4(x-4)=-5x+7 | | 3(6x+2)+5=-109 | | 6(6x+4)+5=-109 | | X+(X*0.2)=100956000 | | -345=-5(8n+5) | | X+(X*0.2)=132019380 | | 3x-48+4x=7x+30 | | -5(8+x)=-20 | | X+(X*0.2)=46055520 |

Equations solver categories